Implementing Exploratory Testing in an Agile Context: A Study Based on Design Science Research - Coutinho, Jarbele C. S.; Andrade, Wilkerson L.; Machado, Patricia (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2023: Anais do VIII Simpósio Brasileiro de Testes de Software Sistemático e Automatizado, 2023)
Exploratory Testing (ET) is a testing technique that has been spreading in the agile environment, as it allows professionals to learn quickly, adjust their tests and, in the process, find software problems that often need to be foreseen in test plans. However, the ET approaches evidenced by the literature are not applicable in the practical context of agile teams. In this sense, this paper proposes a method that facilitates the implementation of ET, considering the agile development scenario, the frequent change in requirements, and the generation of simple and robust artifacts. We use a problem-oriented research method called Design Science Research (DSR). Our main findings are that a method with well-defined activities facilitates the understanding and use of ET in the agile environment.